Clinical characteristics of moderate and severe cases with COVID-19 in Wuhan, China: a retrospective study - Sheng, Lingshuang; Wang, Xiong; Tang, Ning; Meng, Fankai; Huang, Liang; Li, Dengju (Clinical and experimental medicine, 2021)
With the outbreak of COVID-19 ongoing, this infectious disease has been posing a significant threat to public health. However, we are still relatively inexperienced on recognizing the clinical characteristics of severe COVID-19 and death cases. Therefore, we hereby collected and analyzed a total of 232 cases to illustrate the clinical characteristics of such patients in Wuhan and to find notable marks for early clinical warning. We consider age, comorbidities, platelet count, albumin, D-dimer, LDH, CRP and IL-6 level might be more meaningful marks for COVID-19 prognostic evaluation.